Answer:
X to Y: √5
Y to Z: 2√5
Z to X: √13
Step-by-step explanation:
To find the distance between points X(3, 0), Y(4, 2), and Z(6, -2), we can use the distance formula. The distance formula is calculated as follows:
√((x2 - x1)^2 + (y2 - y1)^2)
Let's calculate the distances:
Distance between X and Y:
√((4 - 3)^2 + (2 - 0)^2) = √(1^2 + 2^2) = √(1 + 4) = √5
Distance between Y and Z:
√((6 - 4)^2 + (-2 - 2)^2) = √(2^2 + (-4)^2) = √(4 + 16) = √20 = 2√5
Distance between Z and X:
√((3 - 6)^2 + (0 - (-2))^2) = √((-3)^2 + 2^2) = √(9 + 4) = √13
So, the distances are:
X to Y: √5
Y to Z: 2√5
Z to X: √13